2015
DOI: 10.1103/physrevb.91.094409
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetic phase of the gapless semiconductorV3Al

Abstract: Discovering new antiferromagnetic compounds is at the forefront of developing future spintronic devices without fringing magnetic fields. The antiferromagnetic gapless semiconducting D0 3 phase of V 3 Al was successfully synthesized via arc-melting and annealing. The antiferromagnetic properties were established through synchrotron measurements of the atom-specific magnetic moments, where the magnetic dichroism reveals large and oppositelyoriented moments on individual V atoms. Density functional theory calcul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
24
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 28 publications
3
24
1
Order By: Relevance
“…3,[13][14][15][16] Among the discovered materials, fully compensated ferrimagnetic (FCF) materials have gained a lot of interest recently. [17][18][19] Leuken and Groot showed theoretically that this new class of materials can show 100 % spin polarization without having a net magnetic moment, and hence given the name half metallic antiferromagnetic materials or fully compensated ferrimagnets. 20 However, for the antiferromagnets, symmetry demands the same density of states (DOS) for spin up and spin down bands.…”
Section: Introductionmentioning
confidence: 99%
“…3,[13][14][15][16] Among the discovered materials, fully compensated ferrimagnetic (FCF) materials have gained a lot of interest recently. [17][18][19] Leuken and Groot showed theoretically that this new class of materials can show 100 % spin polarization without having a net magnetic moment, and hence given the name half metallic antiferromagnetic materials or fully compensated ferrimagnets. 20 However, for the antiferromagnets, symmetry demands the same density of states (DOS) for spin up and spin down bands.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast traditional Néel antiferromagnets cannot be spin-polarized due to their symmetric anti-aligned moments resulting in a symmetric DOS, which was demonstrated in the DOS of the gapless semiconductor V 3 Al. [10,11] Unfortunately, recent research has shown that some HMFF compounds tend to be unstable and decompose into more stable states, in addition to possessing properties that are adversely affected by structural disorder. [12][13][14] This current work focuses on the synthesis and characterization of Cr 2 CoAl, which has been predicted to be a HMFF when it adopts the inverse Heusler structure.…”
Section: Introductionmentioning
confidence: 99%
“…1 (lower left). [8,9] The D0 3 Mn 3 Al structure is based on the full Heusler space group Fm3m, which has the formula X 2 YZ where X and Y are equal, leading to the formula X 3 Z. [10] Recently, D0 3 -type V 3 Al was synthesized and determined to behave as a gapless semiconductor, where both the majority (red) and minority (blue) bands in the DOS are symmetric, prohibiting spin polarization as depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%